Karakteristik ekonomi islam dalam al-quran: systematic literature review: Systematic Literature Review - Nafsi, Bella Izzatun (Maliki Interdisciplinary Journal, 2025)
Islamic Economics is based on Islamic teachings that emphasize moral and social values to create justice and welfare. Principles such as the obligation to pay zakat, the prohibition of riba (usury), and fair trade offer sustainable and inclusive solutions to global economic challenges. This study aims to examine the characteristics of Islamic economics found in the Qur’an and how these principles can be implemented in modern economies, particularly in Indonesia. The method used in this study is the Systematic Literature Review (SLR). Eight selected scholarly articles were analyzed to understand how Islamic economic characteristics can be applied in contemporary economic practices. The researcher also visualized bibliometric data using VosViewer, allowing for the relationships between the selected journals to be mapped. The results show that although Islamic economics has been implemented in sectors such as Islamic finance and zakat, there is still significant room for further development, especially in addressing global economic challenges dominated by the capitalist system. Islamic economics offers a more just and ethical approach to creating